Composition of Juvenile Corals on Different Morphotypes of Substrate at Karimunjawa Archipelago, Indonesia - Munasik Munasik; Diah Permata Wijayanti; Retno Hartati; Rudi Pribadi; Yoko Nozawa (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2016)
Patterns of coral recruitment are partially explained by fitness consequences of substrate selection, and may be affected by substrate morphology. This study examined juvenile coral assemblages on morphologically different dead coral substrate in shallow water reefs (4-5 m) at Karimunjawa Island, Java Sea (Indonesia). Surveys on juvenile corals were performed using 0.5×0.5 m transects on two different morphotypes of natural substrate; tabular dead corals (stable) and branching dead corals (unstable). Results showed that the morphological characteristics of dead coral substrate had a significant influence on the generic composition of juvenile corals. Coral recruits on tabular dead coral substrate (stable) which composed micro-cervices was more diverse than on branching dead coral substrate (unstable). Juvenile corals of the genus Acropora were dominant on (exposed microhabitats of) tabular dead coral substrate, while those of the genus Fungia and Montipora were dominant on (cryptic microhabitats of) branching dead coral substrate. These results suggest that Acroporid juveniles can besettled to the various morphotypes of the substrate, thus the distribution pattern of juvenile corals in shallow reef Karimunjawa may correlate with the distribution pattern of natural substrates.Keywords: juvenile, microhabitat, dead coral, substrate Karimunjawa Archipelago